Bicycling and walking in the United States 2010. Benchmarking report. - Steele, Kristen; Altmaier, Monica (My University, 2010)
You can download the report using the following link: http://peoplepoweredmovement.org/site/images/ uploads/2010%20Benchmarking%20FINAL%201.25.09-Web.pdf
Keywords: Fahrradverkehr; Fußgängerverkehr; Verkehrssicherheit; Verkehrsplanung; Erhebung; Vergleich; Verkehrsmittelwahl; Verkehrsverhalten; Mobilität; Verkehrspolitik; Individualverkehr; Fahrradnutzung; Radverkehrsanteil; Fahrradförderung; Gesundheitsförderung; Nichtmotorisierter Verkehr; Verkehrserziehung; Einflussfaktor